LINGUISTIC DEVICES OF STANCE AND DISAGREEMENT IN A POLITICAL INTERVIEW - Ikhsan, Ikhsan; Junaedi, Ahmad; Ahyadi, Ahyadi; Ridwan, Ridwan (Jurnal Education and Development, 2025)
The specific objective of this study was to investigate linguistic device of stance and disalignment markers used by politician in a political interview. This study use a qualitative approach by employing discourse analysis methodology. Data for this study were collected using a transcribed political interview and analysed using the the conventions developed by Du Bois, Schuetze- Coburn, Cumming, and Paolino. The source material for this study consists of a video downloaded from YouTube, which has a total run time of 37 minutes and 54 seconds. The video displayed Jonathan Swan, an Australian political contributor for Axios, conducts interview with President Donald Trump touching various domestic issues in the U.S. The findings show that speakers predominantly express disagreement using negative stance markers ("no," "not," "never"), posing yes/no questions, introducing a third-party to justify a statement, and offering evasive responses. Additional finding is that when they are challenged, the politician tend to change his stance.